The Argon-Argon and sequential stratigraphic correlation methods applied to dating the oldest fossils of the human lineage and the earliest lithic tools from the Pliocene (Turkana Basin, East African Rift) - (:unkn) unknown (My University, 2024)
In the East African Rift, the Plio-Quaternary sedimentary formations of the Turkana Basin (Kenya, Ethiopia) provide one of the oldest and most complete fossil records of the human lineage, including Australopithecus anamensis (4.30–4.10 Ma), Kenyanthropus platyops (3.50–3.20 Ma), Paranthropus aethiopicus (2.53–2.45 Ma), early Homo (2.33 Ma), Paranthropus boisei (2.25–1.72 Ma), and Homo ergaster/Homo erectus (1.75–0.90 Ma). The stratified sediments of this region, with more than 700 meters of accumulated deposits forming the Omo Group, also provide the oldest and longest archaeological record in the world. Lithic cultures date back to 3.3 Ma (Lomekwian), 2.34 Ma (Oldowan), 1.76 Ma (Acheulean), and 0.75 Ma (Levallois). The significance of these discoveries for prehistory is partly due to the ability to attribute them to a specific age. During this presentation, we will discuss how, for more than 40 years, the dating of volcanic deposits in the laboratory and stratigraphic correlations in the field have allowed the dating of very ancient prehistoric sites in the Turkana Basin. The dating of new discoveries, which push the origins of prehistory back to the Pliocene, will be presented as an example.
Keywords: African Research